Role of Salvage Targeted Therapy in Differentiated Thyroid Cancer Patients Who Failed First-Line Sorafenib - Ramona Dadu; Catherine Devine; Mike Hernández; Steven G. Waguespack; Naifa L. Busaidy; Mimi I. Hu; Camilo Jiménez; Mouhammed Amir Habra; Rena V. Sellin; Anita K. Ying; Gilbert J. Cote; Steven I. Sherman; et al. (2014)
Sorafenib, a tyrosine kinase inhibitor, is a common first-line therapy for advanced differentiated thyroid cancer (DTC). However, responses are not durable and drug toxicity remains a problem. The objective of the study was to determine the efficacy of salvage therapy after first-line sorafenib failure. This was a retrospective review at M. D. Anderson Cancer Center from January 2005 to May 2013. The study included patients with metastatic DTC who received salvage therapy after their initial sorafenib failure (group 2). Patients who received first-line sorafenib only (group 1) were evaluated for comparison of overall survival (OS). Progression-free survival, best response, and median OS were measured. Sixty-four patients with metastatic, radioactive iodine refractory DTC were included; 35 were in group 1 and 25 were in group 2, and the groups were well balanced. Median OS of all 64 patients receiving first line sorafenib was 37 months; median OS was significantly longer with salvage therapy compared with sorafenib alone (58 vs 28 months, P = .013). In group 2, 17 patients were evaluable for best response, although two patients had toxicity with sorafenib, which was discontinued before restaging. Best responses with first-line sorafenib were partial response in 2 of 15 (13%), stable disease in 10 of 15 (67%), and progressive disease in 3 of 15 (20%) patients. With salvage therapy, partial responses were seen in 7 of 17 (41%) and stable disease in 10 of 17 (59%) patients. Median progression-free survival was 7.4 months with first-line sorafenib and 11.4 months with salvage therapy. Salvage therapy included sunitinib (n = 4), pazopanib (n = 3), cabozantinib (n = 4), lenvatinib (n = 3), and vemurafenib (n = 3). Other targeted agents are effective salvage treatments after sorafenib failure, despite similar mechanisms of action, and should be offered to patients who are able to receive salvage therapy.